(untitled) (Bangladesh Journal of Urology, 2025)
Introduction & Objectives: Percutaneous nephrolithotomy (PCNL) is a minimally invasive procedure and the gold standard for kidney stone larger than 2cm and complex renal stone. Since it was first introduced, PCNL has been carried out in the prone position. In 1987, Valdivia Uria became the first to introduce PCNL in supine position. Supine PCNL is safe and effective. Good stone approaching calyceal puncture is the key point of success in supine PCNL. We aimed to prove the effectiveness of supine PCNL for management of staghorn stone. Methods: This study is a prospective study conducted in Metropolitan speciality centre for kidney diseases & urology, Chattagram from January 2021 to October 2023. Total 291 patients underwent supine PCNL in which 26 cases were staghorn stone. Out of 26 patient, 6 cases were puncture through lower & middle calyx, rest 20 cases punctured through lower calyx only. All data were collected and statistically analyzed. Result: In demographic characteristics, male was predominate (69.23%). In terms stone characteristics 11 cases were complete staghorn (42.30%) and 15 cases partial staghorn (57.7%). Mean operative time 81.92 min, blood transfusion 69.23%, stone clearance 98.53% , and hospital stay 1-2 . No major complications were observed. Conclusion: Supine position offers potential advantages of better ureteral access, patient handling, simultaneous retrograde and antegrade access, dependent track, easier air way control. Supine PCNL for staghorn stone is safe and effective interm of stone clearence and complications. Bangladesh J. Urol. 2024; 27(1): 62-66